Family education in companion taking medication in patients with diabetes mellitus according to sharia - Farroh Bintang Sabiti; Nur Anna Chalimah Sadyah; Hudan Taufiq (Community Empowerment, 2023)
The prevalence of diabetes mellitus in all age groups continues to increase. One of the problems is medication adherence and blood sugar control. Compliance in drug therapy in patients with diabetes mellitus (DM) aims to control the glycemic index and other clinical outputs and prevent complications. Through educational activities, medication companion cadres (PMO) have increased their knowledge related to DM disease, drug use, and recognition and treatment of drug side effects. Apart from that, PMO families also receive Sharia-based assistance, starting from praying before taking medicine to understanding that only Allah is the healer of all diseases.